„Lyublyu Rossiyu ya…”. The genre tradition of presentation Russia in the lyrical genre of invective - Краковяк, Александра (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The author considers a group of Russian poetic texts aimed at the political foes of Russia as a state. The author argues that these texts are samples of lyrical genre of invective, which is proved by their semantic structure and the objective of the text as a kind of poetic expression. The structure of the genre and its tradition imply a specific image of Russia, which forms in all of the texts analysed, regardless of the literary epoch and political beliefs of the poets.